Adjuvant Treatments of Adult Melanoma: A Systematic Review and Network Meta-Analysis - Jing, Mingyi; Cai, Yi; Shi, Jing; Zhang, Xufan; Zhu, Baohua; Yuan, Fan; Zhang, Jie; Xiao, Min; Chen, Mingling (Frontiers in Oncology, 2022)
Multiple treatments of unresectable advanced or metastatic melanoma have been licensed in the adjuvant setting which causing tremendous interest in developing neoadjuvant strategies for melanoma. The objective of this paper is to investigate the optimum adjuvant treatment for advanced melanoma. We systematically searched databases in PubMed, Cochrane Library, and Embase from inception until January 2022. Eligible studies included those that compared overall survival (OS)/progression-free survival (PFS)/grade 3 or 4 adverse events (AEs) in patients with unresectable advanced or metastatic melanoma. Seven eligible randomized trials with nine publications were included in this study. Direct and network meta-analysis consistently indicated that NIVO+IPI, NIVO, TRAM could significantly improve OS and PFS compared to IPI in advanced melanoma patients. Compared to IPI, NIVO, DTIC, and IPI+gp100 had a reduced risk of grade 3/4 adverse reactions. The NIVO+IPI combination had the highest risk of adverse events, followed by IPI+DTIC and TRAM. Combination therapy was more beneficial to improve OS and PFS than monotherapy in the advanced melanoma treatment, albeit at the cost of increased toxicity. Regarding the OS/PFS, IPI+gp100 ranked below IPI+DTIC and NIVO+IPI, although it had a smaller rate of grade 3 or 4 AEs than other treatments (except NIVO). NIVO is the optimum adjuvant treatment for unresectable advanced or metastatic melanoma with a good risk-benefit profile. In order to choose the best therapy, clinicians must consider the efficacy, adverse events (AEs), and physical status.